The traditional medicine aspects, biological activity and phytochemistry of Arnebia spp. - Amirsaeed Hosseini; Fatemeh Mirzaee; Ali Davoodi; Hossein Bakhshi Jouybar; Mohammad Azadbakht (Medicinski glasnik, 2017)
Arnebia, a sub cosmopolitan and important genus of the Boraginaceae family, comprises 25 species distributed among the world. Based on the studies of Persian medicine texts, there are some promising bioactivities for this genus that is unknown in modern medicine and some of them are still the basis of new remedies. This article presents Arnebia according to the most important ancient information by the most famous Persian medicine books like Makhzan Al Advieh, Tohfat Al-Momenin, Al-Qanun, Al-Seidaneh and Ekhtiarate Badiei. A search of electronic databases including PubMed, Scopus, Science Direct, and Google Scholar was done to find articles published between 1991 and 2017 on pharmacology and phytochemistry of Arnebia spp. In Persian medicine texts, Arnebia's different exclusive forms of preparations are effective for treatment of some disorders such as diarrhoea, amenorrhea, gout, kidney stone, jaundice, chronic fever and burn wounds. There are some activities that are the same in Persian and modern medicine research such as burn wound healing and fever amelioration. Phytochemical investigations on the title genus have led to characterization of many secondary metabolites. Naphthoquinones such as alkannins, shikonins, and their derivatives are the major constituents that have shown pharmacological activities in different Arnebia species. Among the major properties of Arnebia, only two of them (burn healing and fever amelioration) were investigated in modern medicine. The major aforementioned properties discussed in details in ancient sources might be a novel research sources leading to important discoveries in clinical usages of Arnebia.
Keywords: Boraginaceae; Persian medicine; temperament; shikonins; pyrrolizidine alkaloids